2015
DOI: 10.1186/s13017-015-0046-1
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics alone versus appendectomy to treat uncomplicated acute appendicitis in adults: what do meta-analyses say?

Abstract: BackgroundPrimary appendectomy is the current standard of care for treating uncomplicated acute appendicitis, but interest in conservative treatment with antibiotics alone has been increasing in recent years. Clinical trials so far have shown controversial results.MethodsA series of meta-analyses were reviewed. Studies comparing surgery versus antibiotics alone for treating uncomplicated acute appendicitis in adults were included. Descriptive statistics and data on treatment effects were retrieved and summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 38 publications
0
26
0
7
Order By: Relevance
“…The problem with this approach is that the patients are being subjected to high doses of ionizing radiation that may develop years later into cancer or leukemia. In a more recent study [ 26 ], using a series of meta-analysis, it was found that appendectomy was significantly more efficient than antibiotics alone, and that exclusive antibiotic therapy was associated with a higher rate of readmissions, which varied between 14.2 and 20 %. The conclusion of this study was that appendectomy is considered the gold standard for treating uncomplicated acute appendicitis.…”
Section: Treatmentmentioning
confidence: 99%
“…The problem with this approach is that the patients are being subjected to high doses of ionizing radiation that may develop years later into cancer or leukemia. In a more recent study [ 26 ], using a series of meta-analysis, it was found that appendectomy was significantly more efficient than antibiotics alone, and that exclusive antibiotic therapy was associated with a higher rate of readmissions, which varied between 14.2 and 20 %. The conclusion of this study was that appendectomy is considered the gold standard for treating uncomplicated acute appendicitis.…”
Section: Treatmentmentioning
confidence: 99%
“…Many studies analyzing the conservative management of appendicitis have been published. Almost all of these studies looked at managing uncomplicated appendicitis [ 9 11 ], including the use of antibiotics in conservative management. No definite method is currently available to distinguish complicated from uncomplicated appendicitis preoperatively, despite the fact that several studies about predicting complicated appendicitis were published [ 3 , 12 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A further meta-analysis 3 years later with four additional subsequent randomised controlled trials agrees with the aforementioned study, that treatment with antibiotics results in lower complication rates, and in addition, they concluded that treatment with antibiotics produced less pain and a quicker return to work (an important factor in force impact in the military deployed population.) However, with regard to treatment efficacy, treatment failure and readmissions, surgery was still considered to be the gold standard 22. This large evidence base, although may swing in favour of surgical management as the treatment of choice, still reassures the military clinician that in the event of surgery being impossible in the deployed environment, the use of antibiotics is a safe alternative, with the proviso that the patient can be monitored for potential failure of treatment, and may even carry the benefit of a quicker return to duties if successful.…”
Section: Discussionmentioning
confidence: 99%